Modern inhalation anesthetics: Potent greenhouse gases in the global atmosphere. Issue 5 (13th March 2015) - Vollmer, Martin K.; Rhee, Tae Siek; Rigby, Matt; Hofstetter, Doris; Hill, Matthias; Schoenenberger, Fabian; Reimann, Stefan
Abstract: Modern halogenated inhalation anesthetics undergo little metabolization during clinical application and evaporate almost completely to the atmosphere. Based on their first measurements in a range of environments, from urban areas to the pristine Antarctic environment, we detect a rapid accumulation and ubiquitous presence of isoflurane, desflurane, and sevoflurane in the global atmosphere. Over the past decade, their abundances in the atmosphere have increased to global mean mole fractions in 2014 of 0.097ppt, 0.30ppt, and 0.13ppt (parts per trillion, 10 −12, in dry air), respectively. Emissions of these long‐lived greenhouse gases inferred from the observations suggest a global combined release to the atmosphere of 3.1 ± 0.6 million t CO2 equivalent in 2014 of which ≈80% stems from desflurane. We also report on halothane, a previously widely used anesthetic. Its global mean mole fraction has declined to 9.2ppq (parts per quadrillion, 10 −15 ) by 2014. However, the inferred present usage is still 280 ±120t yr −1 . Key Points: Measurements of potent greenhouse gases Emissions for the fluranes are increasing Halothane declines